Analisis Indeks Kelelahan dan Daya Tahan Anaerobic Atlet Futsal SMA Institut Indonesia Semarang - Muh. Isna Nurdin Wibisana (JTIKOR (Jurnal Terapan Ilmu Keolahragaan), 2020)
While futsal is a pre dominant anaerobic endurance sport. Problem research of how the anaerobic endurance ability o extracurricular participants at the Semarang Indonesia Institute High School. The purpose of this study was to determine the anaerobic endurance of extracurricular participants at the Semarang Indonesia Institute High School.This research method uses a descriptive qualitative survey research design. The sample consisted of 16 male students participating in the extracurricular at the Semarang Indonesia Institute High School. The research instrument used the RAST (Running Anaerobic Sprint Test).The result of the study are based on the RAST Test. The test result show that the sample that has an index of fatigue is said to be tired as many as 12 samples (75%) while the samples that have said to be tired are as many as 4 samples (25%). An athlete’s physical condition can be predicted using the right test instrument.Based on data analysis and discussion, it can be concluded that the fatigur index an anaerobic endurance ability of futsal extracurricular participants at the Indonesia Institute of High School Semarang is tired. Test recommendations or endurance testing for futsal sports using Running Anaerobic Sprint Test (RAST)